2014
DOI: 10.1542/peds.2013-3794
|View full text |Cite
|
Sign up to set email alerts
|

Immersion in Water During Labor and Delivery

Abstract: Immersion in water has been suggested as a beneficial alternative for labor, delivery, or both and over the past decades has gained popularity in many parts of the world. Immersion in water during the first stage of labor may be associated with decreased pain or use of anesthesia and decreased duration of labor. However, there is no evidence that immersion in water during the first stage of labor otherwise improves perinatal outcomes, and it should not prevent or inhibit other elements of care. The safety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our results concurred to data reported in a recent Cochrane review, that reported an increase in second degree tears with reduction in episiotomy in women who were in an upright position. [1,10,11] These maternal birth position was typically adopted by pool users and it would seem to influence perineal outcomes. [12]…”
Section: Discussionmentioning
confidence: 99%
“…Our results concurred to data reported in a recent Cochrane review, that reported an increase in second degree tears with reduction in episiotomy in women who were in an upright position. [1,10,11] These maternal birth position was typically adopted by pool users and it would seem to influence perineal outcomes. [12]…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The resulting lack of consensus has made consistent and equitable access to this nonpharmacologic method for pain relief in labor challenging.…”
Section: Editor's Notementioning
confidence: 99%
“… 11 In Australia and the United Kingdom, waterbirth is recognized as an option for healthy women with uncomplicated pregnancies. 12 , 13 , 14 However, obstetric and pediatric colleges in the United States are opposed to waterbirth; 15 , 16 whereas in Canada, they cite a lack of adequate studies to determine safety. 17 Neonatal concerns include fetal temperature rises, 18 , 19 respiratory distress or water aspiration, 20 , 21 infection, 22 , 23 and “snapped” umbilical cords.…”
Section: Introductionmentioning
confidence: 99%